2001
DOI: 10.1080/003655401317074626
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of a Primary Aortic Aneurysm Infected with Shewanella Alga

Abstract: Bacteria of the genus Shewanella are rarely implicated in bacteremia. We report a case of rupture of a primary aneurysm infected with Shewanella alga.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 7 publications
0
19
0
1
Order By: Relevance
“…Shewanella algae is a bacterial species recently identified (23, 24) that is closely related to Shewanella putrefaciens (formerly Pseudomonas putrefaciens) (25). Both S. putrefaciens and S. algae species are rare human pathogens (12,15,25).Recently, we have characterized ␤-lactamase OXA-54 from S. oneidensis and we have shown that this Ambler class D enzyme hydrolyzed imipenem significantly (19). Three S. algae isolates were obtained from clinical samples during the last 2 years from our hospital, and the aim of the present study was to determine their ␤-lactamase content.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Shewanella algae is a bacterial species recently identified (23, 24) that is closely related to Shewanella putrefaciens (formerly Pseudomonas putrefaciens) (25). Both S. putrefaciens and S. algae species are rare human pathogens (12,15,25).Recently, we have characterized ␤-lactamase OXA-54 from S. oneidensis and we have shown that this Ambler class D enzyme hydrolyzed imipenem significantly (19). Three S. algae isolates were obtained from clinical samples during the last 2 years from our hospital, and the aim of the present study was to determine their ␤-lactamase content.…”
mentioning
confidence: 99%
“…Shewanella algae is a bacterial species recently identified (23, 24) that is closely related to Shewanella putrefaciens (formerly Pseudomonas putrefaciens) (25). Both S. putrefaciens and S. algae species are rare human pathogens (12,15,25).…”
mentioning
confidence: 99%
“…S. algae is considered a rare opportunistic pathogen for humans, frequently involving immunocompromised hosts (6,8,9), and are usually part of a polymicrobial infection (6,10,11), which may mask its clinical importance. The presence of chronic leg ulcers in the context of peripheral vascular disease occurs commonly in adults with S. algae SSTI (6,10,12,13), and the affi nity of S. algae for necrotic or ischemic tissues has been well described (12,14,15).…”
Section: Discussionmentioning
confidence: 99%
“…This condition was described in two patients with lower leg ulcers (5). Three other cases of bacteremia have been reported: a patient on hemodialysis developed a case of mixed bacteremia (Escherichia coli and S. algae) (7), an immunocompromised patient with multiple myeloma developed cellulitis in both forearms in association with S. algae bacteremia (9), and a patient suffered a rupture of a primary aneurysm infected with S. algae (13). Ear infections are more common, and a series of 65 cases has been described: patients, mostly children, had acute or chronic otitis media that occurred in the summer (6).…”
Section: Case Reportmentioning
confidence: 99%